The recovery of the effort capacity during training camps - Badea, D. (The European Proceedings of Social & Behavioural Sciences EpSBS, 2016)
This research intends to design a pattern for the recovery of exercise capacity in centralized training sessions. Recovery is a complex process aimed at restoring and overcoming the initial values of homeostasis, pursued in all planning structures, starting from the training lesson (breaks between exercise sessions), continuing with post effort recovery, stage and weekly recovery, and even post-Olympic cycle recovery. Recovery after effort is an increasingly significant component that conditions the athletic performance, being considered a performance reserve. The research is one of practical nature and was conducted over a period of one year. The subjects participating in the research are CSO Pantelimon rugby players, who are also in the National Division of Rugby. The findings of the research resulted from weight control and heart rate measurement. The research methods used were scientific documentation, observation, experiment, measurement, statistical and mathematical method, graphical method. The research results were reflected by developing a recovery pattern for the exercise capacity, able to substantiate accumulations from the centralized training session. The research findings confirm the working hypothesis in the light of the results obtained.